Gain-of-function mutations in interleukin-7 receptor-α (IL7R) in childhood acute lymphoblastic leukemias - Shochat, Chen; Tal, Noa; Bandapalli, Obul Reddy; Palmi, Chiara; Ganmore, Ithamar; te Kronnie, Geertruy; Cario, Gunnar; Cazzaniga, Giovanni; Kulozik, Andreas; Stanulla, Martin; Schrappe, Martin; Biondi, Andrea; et al. (Journal of experimental medicine, 2011)
Interleukin-7 receptor α (IL7R) is required for normal lymphoid development. Loss-of-function mutations in this gene cause autosomal recessive severe combined immune deficiency. Here, we describe somatic gain-of-function mutations in IL7R in pediatric B and T acute lymphoblastic leukemias. The mutations cause either a serine-to-cysteine substitution at amino acid 185 in the extracellular domain (4 patients) or in-frame insertions and deletions in the transmembrane domain (35 patients). In B cell precursor leukemias, the mutations were associated with the aberrant expression of cytokine receptor-like factor 2 (CRLF2), and the mutant IL-7R proteins formed a functional receptor with CRLF2 for thymic stromal lymphopoietin (TSLP). Biochemical and functional assays reveal that these IL7R mutations are activating mutations conferring cytokine-independent growth of progenitor lymphoid cells. A cysteine, included in all but three of the mutated IL-7R alleles, is essential for the constitutive activation of the receptor. This is the first demonstration of gain-of-function mutations of IL7R. Our current and recent observations of mutations in IL7R and CRLF2, respectively suggest that the addition of cysteine to the juxtamembranous domains is a general mechanism for mutational activation of type I cytokine receptors in leukemia.
Gesehen am 30.11.2022